2015
DOI: 10.1126/scisignal.2005846
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase G–regulated production of H 2 S governs oxygen sensing

Abstract: Reflexes initiated by the carotid body, the principal O2-sensing organ, are critical for maintaining cardio-respiratory homeostasis during hypoxia. O2 sensing by the carotid body requires carbon monoxide (CO) generation by heme oxygenase-2 (HO-2) and hydrogen sulfide (H2S) synthesis by cystathionine-γ-lyase (CSE). We report that O2 stimulated the generation of CO, but not that of H2S, and required two cysteine residues in the heme regulatory motif (Cys265 and Cys282) of HO-2. CO stimulated protein kinase G (PK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(128 citation statements)
references
References 47 publications
4
123
0
1
Order By: Relevance
“…These HRMs are independent of the enzymatic active site and bind heme with higher affinity (87). Yuan et al recently substantiated the role of HO-2 and HRMs in redox signaling and demonstrated a role in control of respiratory rate (152). Biochemical and structural NMR studies further supported the conclusion that HRMs in HO-2 allow cellular sensing and response to redox changes (12,42).…”
Section: Localization Of Ho-1 In the Kidneymentioning
confidence: 89%
“…These HRMs are independent of the enzymatic active site and bind heme with higher affinity (87). Yuan et al recently substantiated the role of HO-2 and HRMs in redox signaling and demonstrated a role in control of respiratory rate (152). Biochemical and structural NMR studies further supported the conclusion that HRMs in HO-2 allow cellular sensing and response to redox changes (12,42).…”
Section: Localization Of Ho-1 In the Kidneymentioning
confidence: 89%
“…While ROS resulting from imbalanced expression of HIF-α isoforms mediate the carotid body response to hypoxia, the downstream targets of ROS signaling have not yet been identified. Recent studies implicate carbon monoxide (CO)-sensitive hydrogen sulfide (H 2 S) generation as critical mediators of the carotid body response to hypoxia [18, 38]. Whether altered ROS levels result from dysregulated HIF-α isoform expression target CO and H 2 S signaling in the carotid body remains to be studied.…”
Section: Perspective and Future Directionsmentioning
confidence: 99%
“…O 2 is a potent regulator of CO production from HO-2. Under normoxia, CO production is high whereas CO production is markedly decreased during hypoxia in the carotid body (Peng et al , 2010; Peng et al , 2014a; Yuan et al , 2015). The reduced CO generation, in turn activates CSE-dependent H 2 S synthesis through inhibition of protein kinase G-dependent phosphorylation of CSE (Yuan et al , 2015).…”
Section: Introductionmentioning
confidence: 99%